2005
DOI: 10.7202/705193ar
|View full text |Cite
|
Sign up to set email alerts
|

Paramètres prédictifs de l'apparition des coliformes dans les réseaux de distribution d'eau d'alimentation

Abstract: L'isolement sporadique de coliformes sur certains réseaux de distribution en période chaude et en absnce de tout épisode décelable de contamination (défaut de traitement, post-contamination) laisse supposer que la présence de ces germes dans l'eau pourrait être associée à la présence d'un biofilm important à la surface des canalisations. Cette hypothèse a pu être vérifiée lors de cette étude, réalisée sur différents réseaux de la banlieue parisienne. Ce travail a mis en évidence une relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
1
8
0
2
Order By: Relevance
“…This could possibly explain why AOM had such a positive effect compared to acetate and would suggest that an element necessary for E. coli growth was probably missing in batch reactor containing the dechlorinated drinking water supplemented with acetate. Lastly, although BDOC is classically used to estimate biological stability of water (16,25,26,37,42), our results showed that measuring BDOC concentration is not sufficient to predict the behavior of E. coli in drinking water. It is not the quantity of biodegradable compounds but rather their quality that controls bacterial behavior.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…This could possibly explain why AOM had such a positive effect compared to acetate and would suggest that an element necessary for E. coli growth was probably missing in batch reactor containing the dechlorinated drinking water supplemented with acetate. Lastly, although BDOC is classically used to estimate biological stability of water (16,25,26,37,42), our results showed that measuring BDOC concentration is not sufficient to predict the behavior of E. coli in drinking water. It is not the quantity of biodegradable compounds but rather their quality that controls bacterial behavior.…”
Section: Discussionmentioning
confidence: 72%
“…Better maintenance of E. coli cultivability was also observed when AOM was added; cultivability was even increased after addition of AOM from ozonated algae. AOM, likely to be present in treatment plants during algal blooms, and thus potentially in the treated water may compromise water biological stability.In spite of the disinfection processes, bacterial proliferation can be observed in drinking water distribution network systems (20,26,37,42) proving that certain bacterial populations are able to adapt, transiently or permanently, to the oligotrophic conditions of distribution networks (16,17). This phenomenon has been described for fecal indicators such as coliform bacteria, particularly Escherichia coli (16), and poses the problem of compliance with water quality health regulations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…LeChevallier et al ( , 1996 and later proposed AOC concentrations that should not be exceeded to limit the occurrence of total coliforms in the DS. Using a large full-scale DS database, Volk and Joret (1994) also defined a value of 0.15 mg C/L (BDOC SAND ) as a one of 4 critical thresholds to limit total coliform occurrence along with other parameters. Another threshold value of BDOC SUSP was defined by Servais et al (1995a), it is based on the relationship between the consumption of BDOC observed in the DS and the BDOC content in the treated water of various DSs.…”
Section: Introductionmentioning
confidence: 99%